The Effect of Organisational Culture on Students’ Cognitive, Skill-Based, and Affective Learning Outcomes in Higher Education in Saudi Arabia - Radwan, Omaymah; Bin Abdul Razak, Ahmad Zabidi (Opción, 2019)
The current study aimed to analyze the effect of organizational culture on students cognitive, skill-based and affective learning outcomes in Saudi higher education institutions. It has been conducted a quantitative research methodology by distributing questionnaires which contained 95 items to faculty members at two Saudi higher education institutions. 496 responses were further analysed using the SPSS (V23) and PLS-SEM. Results indica- ted that organisational culture has a direct and significant positive effect on students’ cognitive, skill-based, and affective learning outcomes in the context of Saudi higher education. The present study has a potential to reflect positively on the Ministry of Education, academic leaders, as well as support the higher education institutions.